Pemanfaatan Limbah Minyak Goreng Bekas Melalui Pembuatan Lilin Aromateraphy sebagai Pemanfaatan Waktu Libur Sekolah pada Remaja Masjid Nurul Huda Purworejo Pasir Sakti Lampung Timur - Reni Diah Setiowati; Robi Santoso (Jurnal Informasi Pengabdian Masyarakat, 2024)
This community service is carried out with the aim of providing assistance and counseling to mosque youth in Purworejo village, sub-district. The magical sands of East Lampung. The service is carried out using lecture methods, interactive discussions and direct practice to increase insight, ability and creativity among mosque youth during school holidays. It is hoped that from this assistance and counseling, participants will be able to use their free time during school holidays to fill their classes with useful activities and become creative and innovative young people in utilizing used cooking oil waste which is often thrown away by housewives. The cooking oil waste can be used to make aromatherapy candles. So that the activities carried out can have an effect on improving the economy and increase awareness of cleanliness, environmental health and the dangers of using cooking oil that is used repeatedly.